REVIEW ARTICLE ON LEUCAENA LEUCOCEPHALA AS ONE OF THE MIRACLE TIMBER TREES - Zayed, Mohamed Z.; Sallam, Sobhy M. A.; Shetta, Nader D. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Leucaena leucocephala trees are commonly known as White Lead tree. It is native to Southern Mexico and Northern Central America and spread across many tropical and sub-tropical locations. It has multipurpose uses, such as generation of firewood, timber, greens, fodder, and green manure, as well as to provide shade and control soil erosion. It has been used for medicinal purposes because of possessing multiple pharmacological properties. Studies have shown the presence of various secondary metabolites such as alkaloid, cardiac glycosides, tannins, flavonoids, saponins, and glycosides in this species. In traditional medicine, it is used to control stomach ache and as contraception and abortifacient. In the present study, the global distribution, taxonomy, chemical composition, pharmacological activities, and potential uses of Leucaena leucocephalaare discussed.